Proceedings of the International Conference and the 10th Congress of the Entomological Society of Indonesia (ICCESI 2019) 2020
DOI: 10.2991/absr.k.200513.047
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Load and Flower Constancy of Stingless Bees Tetragonula laeviceps (Smith) and Heterotrigona itama (Cockerell) (Apidae: Meliponinae)

Abstract: Stingless bees are pollinating insects that are important for plants and useful for producing honey. The role of stingless bees as pollinators related to the activity of foraging on flowers. The aim of this study was to measure pollen load and flower constancy of two species stingless bees, Tetragonula laeviceps and Heterotrigona itama in the campus area of IPB University, Bogor. As many as 30 individuals of T. laeviceps and H. itama from different nest colonies were used. Each individual of bee was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
4
4
0
Order By: Relevance
“…Even though there was high diversity of plants grow near the hives, the dominant occurrence of S. lycopersicum pollen indicated that this plant the most visited species by bees in searching for food. This result was in line with the study by Cholis et al (2019) which found that T. laeviceps showed consistency in collecting pollen from Solanaceae plants as much as 70.76%. Another pollen type found in considerable percentage was from coconut tree (Cocos nucifera) which grows around the nest.…”
Section: Variation In Number and Composition Of Plant Species And Famsupporting
confidence: 92%
See 4 more Smart Citations
“…Even though there was high diversity of plants grow near the hives, the dominant occurrence of S. lycopersicum pollen indicated that this plant the most visited species by bees in searching for food. This result was in line with the study by Cholis et al (2019) which found that T. laeviceps showed consistency in collecting pollen from Solanaceae plants as much as 70.76%. Another pollen type found in considerable percentage was from coconut tree (Cocos nucifera) which grows around the nest.…”
Section: Variation In Number and Composition Of Plant Species And Famsupporting
confidence: 92%
“…Meanwhile, the predominant occurrence of Polygonum sp. pollen in line with the report of Cholis et al (2019) that T. laeviceps showed flower constancy in Polygonaceae as part of its foraging behavior.…”
Section: Variation In Number and Composition Of Plant Species And Famsupporting
confidence: 92%
See 3 more Smart Citations